2011
DOI: 10.1097/jcn.0b013e3181f806bc
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Educational Needs for Pain Management of Post-Cardiac Surgery Patients

Abstract: Participants identified the most common pain knowledge gaps for patients before and after discharge after cardiac surgery. These data will be used to develop an education intervention for nurses to help their cardiac surgery patients with more effective pain management strategies before and after discharge home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…In addition, many patients receive analgesics on demand, but only minimal doses, particularly in the case of stronger drugs such as opioids, because nurses are afraid of the side effects of such drugs, including addiction and respiratory depression 19,20. Another barrier to proper pain management indicated by nurses is unsatisfactory access to evidence-based knowledge in the approach to pain management and a lack of support from physicians 2123. Our study showed that a lower level of illness acceptance was associated with greater pain and taking analgesics, which may be due to inadequate pain control.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, many patients receive analgesics on demand, but only minimal doses, particularly in the case of stronger drugs such as opioids, because nurses are afraid of the side effects of such drugs, including addiction and respiratory depression 19,20. Another barrier to proper pain management indicated by nurses is unsatisfactory access to evidence-based knowledge in the approach to pain management and a lack of support from physicians 2123. Our study showed that a lower level of illness acceptance was associated with greater pain and taking analgesics, which may be due to inadequate pain control.…”
Section: Discussionmentioning
confidence: 69%
“…In cognitively impaired or nonverbal patients, information from caregivers or family on the patient's behaviors may aid pain assessments 9 . Nevertheless, patient self‐reporting is generally viewed as more reliable than external observation and is ranked first in the hierarchy of pain assessment techniques 9,12 . Pain assessments should also include pain location, quality, type (eg, visceral, neuropathic), 9,13 and cause 9 .…”
Section: Assessment Of Painmentioning
confidence: 99%
“…Afterward, in‐hospital recovery assessments tend to focus on pain and restoration of more complex physiologic functions 3 . Patients’ expectations may be unrealistic regarding recovery, 12 and it is important for nurses to be familiar with the typical patterns of recovery, and recognize that patient age and comorbidities may have an effect 25,26 . The patient should understand that for most surgical procedures, at least some pain is to be expected 27 .…”
Section: Assessment Of Painmentioning
confidence: 99%
“…Sykepleier har et undervisende ansvar (7). God og tilpasset informasjon til pasienter som står i fare for å utvikle, eller allerede har utviklet, CIPP, kan i mange tilfeller avdekke pasienters misoppfatninger og redsler (8).…”
Section: Sykepleietiltak Ved Cippunclassified